The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1124/mol.108.051516
|View full text |Cite
|
Sign up to set email alerts
|

Copper Regulation of Hypoxia-Inducible Factor-1 Activity

Abstract: Copper deficiency suppresses and copper addition enhances the expression of vascular endothelial growth factor (VEGF), which is primarily controlled by hypoxia‐inducible factor 1 (HIF‐1) transcription factor. The regulatory subunit of HIF‐1α senses oxygen availability and is also affected by various transition metals. The purpose of this study was to determine whether or not copper is required for activation of HIF‐1. Copper depletion by copper chelator tetraethylenepentamine (TEPA) decreased the hypoxia‐induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
206
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(213 citation statements)
references
References 47 publications
(61 reference statements)
5
206
0
2
Order By: Relevance
“…In addition, copper-dependent amino oxidases are inhibited by TETA. Copper and/or iron chelation affects the regulation and the functions of hypoxia-inducible factor 1␣, and its potential interaction with SSAT1/2 renders TETA action very complicated (Baek et al, 2007a,b;Feng et al, 2009). In light of the previous and present findings, it is clear that additional studies with TETA and SpmTrien in animal models of type 2 diabetes and cancer models are warranted (Yu et al, 2006;Gupte and Mumper, 2009;Lu et al, 2010Lu et al, , 2010a.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In addition, copper-dependent amino oxidases are inhibited by TETA. Copper and/or iron chelation affects the regulation and the functions of hypoxia-inducible factor 1␣, and its potential interaction with SSAT1/2 renders TETA action very complicated (Baek et al, 2007a,b;Feng et al, 2009). In light of the previous and present findings, it is clear that additional studies with TETA and SpmTrien in animal models of type 2 diabetes and cancer models are warranted (Yu et al, 2006;Gupte and Mumper, 2009;Lu et al, 2010Lu et al, , 2010a.…”
Section: Discussionmentioning
confidence: 65%
“…However, the novel cellular targets of TETA are expected to explain the physiological background of its therapeutic potential in many diseases. Thus, detailed structure-activity studies using structural analogs closely resembling TETA are definitely warranted in distinct disease models to understand its drug action (Feng et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…85 According to recent studies, cobalt-induced stabilization of Hif-1α is dependent on copper. 86,87 Furthermore, copper supplementation reversed contractile dysfunction and prevented transition to heart failure in pressure-overloaded mice, at least in part through promotion of myocardial angiogenesis. 88 In addition to cobalt and copper function, several approved drugs have been reported to affect myocardial angiogenesis.…”
Section: Therapeutic Myocardial Angiogenesis As a Potential Therapy Fmentioning
confidence: 99%
“…Among these metals is copper (van Heerden et al, 2004;Martin et al, 2005). However, other studies have demonstrated that copper is required for HIF-1 transcriptional activity under hypoxic conditions in addition to its inhibitory action on prolyl hydroxylases (Feng et al, 2009). This observation raises an interesting question: is copper required for HIF-1 transcriptional activity under the condition of exposure to transition metals including cobalt?…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of copper on HIF-1 transcriptional activity involves its role in the interaction between HIF-1 and the hypoxia-responsive element (HRE) sequence of target genes and the formation of HIF-1 transcriptional complex (Feng et al, 2009). These processes take place in the nucleus, thus copper has to be transported into the nucleus to ensure the transcriptional activity of HIF-1.…”
Section: Introductionmentioning
confidence: 99%